Low-temperature high-thermal-conductivity nano-silver adhesive as well as preparation method and application thereof
By preparing low-temperature high-thermal nanosilver adhesives under low temperature conditions, the problem of material performance damage caused by high-temperature use in the prior art is solved, high thermal conductivity and good bonding strength are achieved, the needs of new semiconductor packaging materials are met, and the preparation process is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202510079043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
When used under high temperature conditions, existing low-temperature nano-silver adhesives are easily damaged in material performance, and the preparation process is complex and costly, making it difficult to meet the high-demand application needs.
Using a low-temperature high-thermal nanosilver adhesive preparation method, a stable dispersion liquid is formed by mixing the dispersant and the metal powder at a specific temperature and stirring time, and the adhesive is obtained by vacuum degassing. This method realizes sintering at low temperatures to avoid damage to the material by high temperatures.
It achieves high thermal conductivity and good bonding strength under low temperature conditions, meets the needs of new semiconductor packaging materials, simplifies the preparation process and reduces costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano silver, and in particular to a high-temperature thermal conductive nano silver adhesive and a preparation method and application thereof. Background Art
[0002] As a new type of material, low-temperature nanosilver adhesive has shown great application potential in many fields due to its unique properties. It not only has the bonding function of traditional adhesives, but also integrates the special properties of nanosilver to achieve good bonding effects under low temperature conditions, bringing innovative solutions to the electronics, medical and other industries. Its main advantages are as follows: 1. High conductivity Nanosilver particles have excellent electrical properties, with small particle size, large specific surface area and short electron transmission path. In low-temperature nanosilver adhesives, nanosilver particles are interconnected to form a conductive network, which gives the adhesive good conductivity. For example, in the connection of electronic devices, this high conductivity can ensure fast and stable signal transmission, reduce resistance and reduce energy loss, which is crucial for high-speed chips and circuit components.
[0003] 2. Low temperature sintering characteristics Unlike traditional high-temperature sintering materials, low-temperature nanosilver adhesives can be sintered at relatively low temperatures (usually 150-250°C). This feature greatly broadens its application range, especially for some temperature-sensitive materials such as plastic substrates, organic electronic components, etc. In the bonding process of these materials, low-temperature sintering avoids the damage to material properties caused by high temperature, ensuring the integrity and performance stability of the device.
[0004] 3. Good bonding strength Nanosilver adhesives can show high bonding strength to a variety of materials, such as metals, ceramics, glass and polymers. Nanosilver particles form strong bonding forces with the surface of the adhered material through physical adsorption and chemical reaction. In electronic packaging, it can firmly connect the chip to the substrate, ensuring that the connection remains stable in complex working environments (such as vibration, temperature changes, etc.) without loosening or falling off.
[0005] The preparation methods of low-temperature nano silver adhesives mainly include: 1. Chemical reduction method This is one of the commonly used methods for preparing low-temperature nanosilver adhesives. First, a silver salt (such as silver nitrate) is dissolved in an appropriate solvent to form a silver ion solution. Then, a reducing agent (such as sodium citrate, sodium borohydride, etc.) is added to reduce the silver ions to nanosilver particles under certain temperature, stirring speed and reaction time conditions. At the same time, a stabilizer (such as polyvinyl pyrrolidone) is added to prevent the agglomeration of nanosilver particles to obtain nanosilver colloids with uniform particle size and good dispersibility. Finally, the nanosilver colloid is mixed with an organic adhesive (such as epoxy resin, acrylic resin, etc.), and the nanosilver particles are uniformly dispersed in the adhesive matrix by ultrasonic dispersion and other means to obtain a low-temperature nanosilver adhesive.
[0006] 2. Physical vapor deposition In a high vacuum environment, the silver source is heated and evaporated into gaseous atoms. These gaseous silver atoms are transported to the surface of the substrate containing an organic binder under the action of a carrier gas. On the surface of the substrate, the silver atoms condense and deposit to form nanosilver particles, and at the same time fuse with the organic binder. The particle size of the nanosilver particles prepared by this method is controllable and is tightly bonded to the binder. However, the equipment cost is high, the process is complex, and the output is relatively low.
[0007] 3. Electrochemical deposition method With silver as the anode, in an electrolyte containing silver ions, a certain voltage is applied so that the silver ions are reduced to nanosilver particles by electrons on the surface of the cathode (usually a substrate coated with an organic adhesive). By controlling parameters such as current density, deposition time, and electrolyte composition, the particle size and deposition amount of the nanosilver particles can be precisely controlled. The nanosilver adhesive prepared by this method has a relatively uniform distribution of nanosilver particles in the adhesive and is firmly bonded, but it has high requirements for equipment and operation.
[0008] Due to its excellent performance, the application areas of low-temperature nanosilver adhesives are mainly as follows: 1. Chip packaging During chip packaging, low-temperature nanosilver adhesive is used to connect the chip to the substrate. Its high conductivity ensures good electrical connection between the chip and the external circuit, and its low-temperature sintering characteristics avoid high temperature damage to chip performance. Compared with traditional solder, nanosilver adhesive can achieve finer connections, improve packaging density, enhance the reliability of the packaging structure, and extend the service life of the chip.
[0009] 2. Flexible Electronics With the development of flexible electronic technology, higher requirements are placed on the connection between flexible materials. Low-temperature nanosilver adhesive can achieve the bonding of flexible substrates (such as polyimide, polyester, etc.) and flexible conductive circuits at low temperatures, and can still maintain good conductivity and bonding strength under deformation conditions such as bending and stretching. This makes it widely used in wearable devices, flexible display screens and other fields.
[0010] 3. Medical equipment assembly In the manufacture of medical devices, various materials (such as metal, plastic, glass, etc.) need to be bonded. The good bonding strength and antibacterial properties of low-temperature nanosilver adhesives make them an ideal choice. For example, in the assembly of disposable medical devices such as syringes and infusion tubes, it can not only ensure a firm connection between components, but also prevent bacterial growth and reduce the risk of infection.
[0011] 4. Optical field In the assembly of optical devices, such as optical fiber connection and optical lens fixing, an adhesive is needed that can ensure bonding strength without affecting optical performance. Low-temperature nanosilver adhesive cures at low temperatures and does not cause thermal damage to optical components. Its high transparency and low light absorption meet the requirements of the optical field and can ensure efficient transmission of optical signals.
[0012] 5. Aerospace Aerospace equipment has extremely high requirements for material performance. The high bonding strength, good conductivity and high temperature resistance of low-temperature nanosilver adhesives make them potentially useful in the connection of aerospace electronic equipment and the bonding of composite materials. It can achieve rapid bonding in low-temperature environments, meeting the requirements of the aerospace field for low-temperature adaptability and reliability of materials.
[0013] CN 118755428 A relates to a fast-curing conductive silver glue and its production process. The raw materials include the following weight parts: 35-40 parts of base resin, 8-10 parts of curing agent, 65-70 parts of conductive filler, 3-5 parts of auxiliary agent, and 0.3-0.5 parts of catalyst; wherein the base resin is liquid bisphenol F type resin; the conductive filler includes the following weight parts of filler composition: 20-30 parts of nano spherical silver powder, 60-70 parts of silver-coated graphene oxide; the sphericity of the nano spherical silver powder is 8.8-9.0; the D50 of the nano spherical silver powder is 20-30nm; the D50 of the silver-coated graphene oxide is 00-200 μm; the catalyst is selected from any one of dimethylaminophenol or 2-ethyl-4-methylimidazole; in the silver-coated graphene oxide, the silver coating layer is coated in an island shape on the surface of the graphene oxide base. The above formula ingredients are complex and it is difficult to achieve the technical effect of the present application. Summary of the invention
[0014] The object of the present invention is to provide a method for preparing a low-temperature and high-thermal-conductivity nanosilver adhesive, comprising the following steps: S11: adding the dispersant to the solvent, stirring for 30 min at a temperature between 40 and 50°C to form a stable dispersion; S12: adding the metal powder to the dispersion obtained in step S11, stirring for 30 to 60 minutes at a temperature between 30° C. and 40° C., and mixing evenly to obtain a mixed solution; S13: removing dissolved gas from the mixed solution obtained in step S12 by vacuum to obtain a low-temperature high-thermal-conductivity nano-silver adhesive, wherein the low-temperature high-thermal-conductivity nano-silver adhesive is stored at a temperature between -35 and -45°C.
[0015] Furthermore, in step S11, the dispersant is one of polyvinyl alcohol, acrylate or polyacrylamide. When the dispersant is polyacrylamide, after the dispersant is dissolved between 40 and 50° C., the obtained dispersion has a higher viscosity, which is more conducive to uniform mixing of the metal powder in the dispersion, and the metal powder is not easy to agglomerate, resulting in a better effect.
[0016] Furthermore, in step S11, the solvent is ethylene glycol or diisobutyl carbinol. When the solvent is diisobutyl carbinol, due to its high molecular weight and high kinematic viscosity, the metal powder is more evenly distributed in the dispersion, and the low-temperature and high thermal conductivity nanosilver adhesive finally prepared has better application performance.
[0017] Furthermore, in step S11, the mass of the dispersant is 5-20% of the mass of the solvent.
[0018] Furthermore, the metal powder in step S12 is one of nano silver powder, nano copper silver-plated powder or nano gold silver-plated powder, the particle size of the metal powder is 20-100 nm, the silver is plated on the surface of copper, the mass of copper is 5-30% of the mass of silver, the silver in the nano gold silver-plated powder is plated on the surface of gold, the mass of gold is 0.5-5% of the mass of silver, when the metal powder is nano copper silver-plated powder, the performance is slightly decreased but the cost is lower, when the metal powder is nano gold silver-plated powder, the performance is slightly improved but the cost is higher, which is suitable for high-requirement scenarios.
[0019] Furthermore, the mass of the metal powder in step S12 is 18 to 20 times the mass of the solvent in step S11.
[0020] The present invention also provides a low-temperature and high-thermal-conductivity nano-silver adhesive prepared by using the above-mentioned preparation method of the low-temperature and high-thermal-conductivity nano-silver adhesive.
[0021] In addition, the present invention also provides an application of the above-mentioned low-temperature and high-thermal-conductivity nano-silver adhesive, comprising the following steps: S21: Coating and positioning of low-temperature and high-thermal-conductivity nanosilver adhesive: The low-temperature and high-thermal-conductivity nanosilver adhesive that has been warmed up at room temperature for 60 minutes is evenly coated on the connection surface of the chip or substrate, and the position of the chip and the substrate is set by a die bonding machine to ensure accurate alignment of the chip and the substrate; S22: Sintering process: The chip coated with low-temperature and high-thermal-conductivity nanosilver adhesive is attached to the substrate and placed in a sintering furnace. It is sintered at a temperature between 260 and 360°C and a pressure between 8 and 12 MPa to form a dense metal layer, thereby achieving metallurgical bonding between the chip and the substrate.
[0022] The low-temperature and high-thermal-conductivity nanosilver adhesive prepared by the invention is applied to new semiconductor-specific packaging materials, has good thermal conductivity and bonding strength, meets the packaging requirements of new semiconductors, has a simple preparation process, and is easy to promote and apply. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with embodiments. The present invention is not limited to the embodiments. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention. Example 1
[0024] A method for preparing a low-temperature and high-thermal-conductivity nanosilver adhesive comprises the following steps: S11: Add 1 g of polyvinyl alcohol to 5 g of ethylene glycol, stir for 30 min at a temperature between 40 and 50 °C to form a stable dispersion; S12: adding 95 g of nano silver powder with a particle size of 20-100 nm to the dispersion obtained in step S11, stirring for 40 min at a temperature between 30° C. and 40° C. to obtain a mixed solution; S13: removing dissolved gas from the mixed solution obtained in step S12 by vacuum to obtain a low-temperature high-thermal-conductivity nano-silver adhesive, wherein the low-temperature high-thermal-conductivity nano-silver adhesive is stored at a temperature between -35 and -45°C.
[0025] The low-temperature and high-thermal-conductivity nano-silver adhesive prepared above and stored at low temperatures is applied to a new semiconductor-specific packaging material, comprising the following steps: S21: Coating and positioning of low-temperature and high-thermal-conductivity nanosilver adhesive: The low-temperature and high-thermal-conductivity nanosilver adhesive that has been warmed up at room temperature for 60 minutes is evenly coated on the connection surface of the chip or substrate, and the position of the chip and the substrate is set by a die bonding machine to ensure accurate alignment of the chip and the substrate; S22: Sintering process: The chip coated with low-temperature and high-thermal-conductivity nanosilver adhesive is attached to the substrate and placed in a sintering furnace. It is sintered at a temperature between 320 and 330°C and a pressure between 9 and 10 MPa to form a dense metal layer, thereby achieving metallurgical bonding between the chip and the substrate. Example 2
[0026] A method for preparing a low-temperature and high-thermal-conductivity nanosilver adhesive comprises the following steps: S11: Add 1 g of acrylate to 5 g of ethylene glycol, stir for 30 min at a temperature between 40 and 50 °C to form a stable dispersion; S12: adding 95 g of nano silver powder with a particle size of 20-100 nm to the dispersion obtained in step S11, stirring for 40 min at a temperature between 30° C. and 40° C. to obtain a mixed solution; S13: removing dissolved gas from the mixed solution obtained in step S12 by vacuum to obtain a low-temperature high-thermal-conductivity nano-silver adhesive, wherein the low-temperature high-thermal-conductivity nano-silver adhesive is stored at a temperature between -35 and -45°C.
[0027] The low-temperature and high-thermal-conductivity nano-silver adhesive prepared above and stored at low temperatures is applied to a new semiconductor-specific packaging material, comprising the following steps: S21: Coating and positioning of low-temperature and high-thermal-conductivity nanosilver adhesive: The low-temperature and high-thermal-conductivity nanosilver adhesive that has been warmed up at room temperature for 60 minutes is evenly coated on the connection surface of the chip or substrate, and the position of the chip and the substrate is set by a die bonding machine to ensure accurate alignment of the chip and the substrate; S22: Sintering process: The chip coated with low-temperature and high-thermal-conductivity nanosilver adhesive is attached to the substrate and placed in a sintering furnace. It is sintered at a temperature between 320 and 330°C and a pressure between 9 and 10 MPa to form a dense metal layer, thereby achieving metallurgical bonding between the chip and the substrate. Example 3
[0028] A method for preparing a low-temperature and high-thermal-conductivity nanosilver adhesive comprises the following steps: S11: Add 0.5 g of polyacrylamide to 5 g of diisobutyl carbinol, stir for 30 min at a temperature between 40 and 50 °C to form a stable dispersion; S12: adding 95 g of nano silver powder with a particle size of 20-100 nm to the dispersion obtained in step S11, stirring for 40 min at a temperature between 30° C. and 40° C. to obtain a mixed solution; S13: removing dissolved gas from the mixed solution obtained in step S12 by vacuum to obtain a low-temperature high-thermal-conductivity nano-silver adhesive, wherein the low-temperature high-thermal-conductivity nano-silver adhesive is stored at a temperature between -35 and -45°C.
[0029] The low-temperature and high-thermal-conductivity nano-silver adhesive prepared above and stored at low temperatures is applied to a new semiconductor-specific packaging material, comprising the following steps: S21: Coating and positioning of low-temperature and high-thermal-conductivity nanosilver adhesive: The low-temperature and high-thermal-conductivity nanosilver adhesive that has been warmed up at room temperature for 60 minutes is evenly coated on the connection surface of the chip or substrate, and the position of the chip and the substrate is set by a die bonding machine to ensure accurate alignment of the chip and the substrate; S22: Sintering process: The chip coated with low-temperature and high-thermal-conductivity nanosilver adhesive is attached to the substrate and placed in a sintering furnace. It is sintered at a temperature between 320 and 330°C and a pressure between 9 and 10 MPa to form a dense metal layer, thereby achieving metallurgical bonding between the chip and the substrate. Example 4
[0030] The polyacrylamide in Example 3 is replaced by polyvinyl alcohol, and the rest is the same as Example 3 and will not be described in detail. Example 5
[0031] The nano silver powder in Example 1 is replaced by nano gold-plated silver powder, the mass of gold is 10% of the mass of silver, and the rest is the same as Example 1 and will not be repeated here. Example 6
[0032] The nano silver powder in Example 1 is replaced by nano copper silver-plated powder, and the mass of copper is 10% of the mass of silver. Other details are the same as in Example 1 and will not be described again. Example 7
[0033] The diisobutyl carbinol in Example 3 is replaced by ethylene glycol, and the rest is the same as Example 3 and will not be described in detail.
[0034] Comparative Example 1
[0035] The step of vacuum removal of dissolved gas from the mixed solution in Example 3 is removed, and the rest is the same as Example 3 and will not be described in detail.
[0036] The low-temperature and high-thermal-conductivity nanosilver adhesive prepared in the above examples and comparative examples was applied to a new semiconductor packaging material, and the performance was tested. The test results are shown in Table 1. The thermal conductivity test refers to GB / T 10294-2008 "Thermal conductivity test method - thermal conductivity determination method"; the bonding strength test method: the shear strength of the joint between the chip and the substrate interconnected by the low-temperature and high-thermal-conductivity nanosilver adhesive is obtained by a thrust machine (100kg) test, and the chip with a connection area of 2.9mm×2.9mm is tested. The test process is based on the thrust test standard JESD22-B117A.
[0037] Table 1 Test items Thermal conductivity, W / (m·K) Bond strength, MPa Example 1 374 58 Example 2 373 57 Example 3 381 59 Example 4 375 58 Example 5 382 60 Example 6 372 56 Example 7 373 56 Comparative Example 1 355 52 As can be seen from the data in the above table, the low-temperature and high-thermal-conductivity nanosilver adhesives prepared in Examples 1 to 7 are applied to new semiconductor-specific packaging materials, and the performance is tested. The results show that both thermal conductivity and bonding strength are better, meeting the packaging requirements of new semiconductors. The data of Example 7 show that the solvent diisobutyl carbinol has better technical effects, the data of Example 4 show that the dispersant polyacrylamide has better technical effects, the data of Example 5 show that the nano-gold silver-plated powder has better technical effects, and the data of Example 6 show that the nano-copper-gold silver-plated powder has slightly worse technical effects, but can meet the packaging requirements and has lower costs. The data of Comparative Example 1 show that vacuum removal of dissolved gases in the mixed solution is conducive to enhancing the technical effects of the product.
Claims
1. A method for preparing a low-temperature and high-thermal-conductivity nanosilver adhesive, characterized in that: The steps include: S11: adding the dispersant to the solvent, stirring for 30 min at a temperature between 40 and 50°C to form a stable dispersion; S12: adding the metal powder to the dispersion obtained in step S11, stirring for 30 to 60 minutes at a temperature between 30° C. and 40° C., and mixing evenly to obtain a mixed solution; S13: removing dissolved gas from the mixed solution obtained in step S12 by vacuum to obtain a low-temperature high-thermal-conductivity nano-silver adhesive, wherein the low-temperature high-thermal-conductivity nano-silver adhesive is stored at a temperature between -35 and -45°C.
2. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 1, characterized in that: In the step S11, the dispersant is one of polyvinyl alcohol, acrylate or polyacrylamide.
3. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 1, characterized in that: In the step S11, the solvent is ethylene glycol or diisobutyl carbinol.
4. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 1, characterized in that: The mass of the dispersant in step S11 is 5-20% of the mass of the solvent.
5. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 1, characterized in that: The metal powder in step S12 is one of nano silver powder, nano copper silver-plated powder or nano gold silver-plated powder, and the particle size of the metal powder is 20-100 nm.
6. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 1, characterized in that: The mass of the metal powder in step S12 is 18 to 20 times the mass of the solvent in step S11.
7. The method for preparing the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 5, characterized in that: In the nano copper silver-plated powder, silver is plated on the surface of copper, and the mass of copper is 5-30% of the mass of silver. In the nano gold silver-plated powder, silver is plated on the surface of gold, and the mass of gold is 0.5-5% of the mass of silver.
8. A low-temperature and high-thermal-conductivity nano-silver adhesive prepared by the method for preparing the low-temperature and high-thermal-conductivity nano-silver adhesive according to any one of claims 1 to 7.
9. The use of the low-temperature and high-thermal-conductivity nanosilver adhesive according to claim 8, characterized in that: The following steps are involved: S21: Coating and positioning of low-temperature and high-thermal-conductivity nanosilver adhesive: The low-temperature and high-thermal-conductivity nanosilver adhesive that has been warmed up at room temperature for 60 minutes is evenly coated on the connection surface of the chip or substrate, and the position of the chip and the substrate is set by a die bonding machine to ensure accurate alignment of the chip and the substrate; S22: Sintering process: The chip coated with low-temperature and high-thermal-conductivity nanosilver adhesive is attached to the substrate and placed in a sintering furnace. It is sintered at a temperature between 260 and 360°C and a pressure between 8 and 12 MPa to form a dense metal layer, thereby achieving metallurgical bonding between the chip and the substrate.